Globalisation of stone tools and beginnings of mechanical processing of polymers - Čatić, Igor; Rujnić-Sokele, Maja; Karavanić, Ivor (2010)
Based on research on influence of rubber and plastics on globalization, an interesting question arose: can we define the first globalization way of material culture? Manufacturing of first stone tools can be seen at the site of Gona, Ethiopia (dated to 2, 6 million years ago), followed by several sites including the evidence from West Turkana in Kenya (2, 34 ± 0, 4 million years ago), Olduvai in Tanzania and Sterkfontain in South Africa (2 – 1, 6 million years ago). The products found at the sites were simple stone choppers, chopping tools and flakes. We used synthesiological approach and combined the knowledge from archaeology, production technology and the field of polymers in order to approach the interesting question relating to the aforementioned finds: for which purpose these tools were used? Firstly, the manufactured stone tools were used for procedures such as breaking of the natural polymers: e.g. crushing of the larger bones in order to obtain the marrow, and for butchering of animals.
Projekt MZOS
Projekt MZOS
ENG